POLITICAL CORRUPTION PREVENTION IN REGIONAL ELECTION AFTER THE DECISION OF THE CONSTITUTIONAL COURT NO. 33/PUU-XII/2014 - Fajar Laksono Soeroso (Asia Pacific Fraud Journal, 2016)
Political dynasty in the regional election in Indonesia has been canceled by the Constitutional Court (MK). In fact, the political dynasty is considered as elements that undermine the promotion of democracy and anti-corruption culture in Indonesia. Moreover, in case of corruption, political dynasty has a very close relationship with corruption, or commonly known as political corruption. By law, a political dynasty can no longer be resisted. Therefore, what is needed is how to prevent or at least to minimize the political corruption committed by the incumbent. This paper is set in 3 sub-headings, namely (a) corruption in Regional Elections: (b). Political Corruption by Incumbent; and (c) Political Corruption Prevention. Based on the analysis performed, the incumbent has broad access in economic, social, and politics which can provide a personal benefit to him or win his group in the elections. Therefore, the prevention of political corruption can be focused on (1) the financial preparedness and the control of campaign funds; (2) the opening of a space for people to demand commitment, consistency of attitude, and integrity of the incumbent in the fight against political corruption; and (3) enforcement of the rules must be carried out firmly without compromise